A burglar's guide to the city - Manaugh, Geoff (Farrar, Straus and Giroux, 2016)
Space invaders -- Crime is a way to use the city -- Your building is a target -- Tools of the trade -- Deep inside -- A crime is nothing if you can't get away -- Burglary requires architecture